Paint and Coatings Industry - Yilmaz, Faris (IntechOpen, 2019)
Some of the futuristic applications are nanotubes for electrically conductive coatings and to increase the rate of reaction of thermoset resins; organosilane dendrimer coatings; buckyball coatings for machine parts; and metals for conductive coatings in inks. The technology is limited to substantially specialized applications due to the high cost per unit volume needed to reduce the size of the particles and the need to add surface modifiers to prevent the particles from agglomerating. Recent research efforts focus primarily on the functionalization of the particle surface of the nanoparticles to make them more compatible with the coating resin systems, so that easy dispersion, low viscosity, and covalent bonding are provided between the particles and the resins.